HYDRAULIC DESIGN OF THE SURAMANA DAM â SULAWESI TENGAH - Sembiring, Jeremia
Most of the residents of Surumana Village make a living in the agricultural and plantation sectors, so they need a lot of water in their daily lives. Planning for the Surumana Dam in the Surumana Watershed can be a solution in the context of providing clean water on a large scale. The dam can also function as a reservoir for flood control, provider of irrigation water, hydropower, and other benefits so that it can help improve the economy in Donggala Regency. The focus in this major task is to design a diversion structure that can divert river flow during construction and to analyze Flood Routing in spillway. Preliminary studies of hydrological, topographical, and geological analyzes are required to determine the design flood hydrograph. For flood hydrograph analysis, the synthetic unit hydrograph method HEC-HMS (Snyder) was chosen. In the planning analysis of the diversion tunnel dimensions, a flood discharge of Q25 was used of 531.4 m3/s. With a cofferdam elevation of 70 meters, a 5.5 meter diameter diversion tunnel was chosen with a standard horse shoe section. In the design of the spillway, the shape of the Ogee type-I was chosen with an upright upstream with a crest elevation at an elevation of 90 meters. In the planning of the stilling basin, a flood discharge of Q100 is used and the type of stilling basin is USBR IV. The results of flood routing through the spillway with QPMF obtained a decrease in peak flood discharge from 2350.4 m3/s to 2141.5 m3/s with the peak elevation still below the dam elevation.